2013
DOI: 10.3109/08039488.2013.780259
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic traits in a representative sample of Finnish male prisoners

Abstract: The PCL-R is a reliable and valid measure of the psychopathy construct of the Finnish male prisoners. The PCL-R is applicable to the Finnish offenders and it is a useful tool for assessing psychopathy in the Finnish criminal justice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…The authors found that the level of psychopathic traits did not significantly differ between the patients with arsons and those with other criminal acts. In our sample, the level of psychopathic traits seemed to be slightly lower than reported previously among Finnish prisoners (mean 19.5, SD 8.05) [ 48 ].…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The authors found that the level of psychopathic traits did not significantly differ between the patients with arsons and those with other criminal acts. In our sample, the level of psychopathic traits seemed to be slightly lower than reported previously among Finnish prisoners (mean 19.5, SD 8.05) [ 48 ].…”
Section: Discussioncontrasting
confidence: 76%
“…However, only 1.6% of the firesetters scored 30 points or more, which is the original cut-off score of psychopathy by Hare [ 31 ]. The proportion of these highly psychopathic persons seems to be smaller in the present sample than in a Finnish prison population in general (12.3%) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale has dimensional characteristics consisting of two intercorrelated factors. The first factor assesses affective insensitivity while the second emphasizes antisocial behavior (Hare, 2003;Lindberg et al, 2009;Laajasalo et al, 2013;Jüriloo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood psychosocial adversities and maladjustment have previously been linked to a number of negative outcomes over the life time, including antisocial behaviors (12,13). Among children with ASD, Howlin and Clements (14) found abuse to be associated with more behavioral difficulties, including aggression, compared to typically developed children. Similarly, Allely et al (15) have described the presence of a broad range of adverse contextual factors among individuals with ASD who commit serious violent crimes.…”
Section: Introductionmentioning
confidence: 99%